Impression management in the workplace: Research, theory and practice - J. Dubrin, Andrew; Harun, Minah (Universiti Utara Malaysia, 2011)
A good comprehensive book is a rare find.If you are searching endlessly for a book that has it all, this is the one that presents every bit about impression management that one must know to get by in today’s world of advanced technology where everything is at our finger tips.The content covers from the most basic, that is, the meaning and nature of impression management (Chapter One), to the most complex yet a significant area that deals with the functional and dysfunctional consequences of impression management (Chapter Eleven).